DUKUNGAN TERHADAP KEKERASAN: MENGUJI IDENTITAS SOSIAL DAN PERSEPSI KETERANCAMAN - GAZI SALOOM (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
This study aimed at examining the impact of social identification and threat perception on public supports for violence. This study employed quantitative method involving 198 students of Syarif Hidayatullah State Islamic University of Jakarta. Supports for violence was measured by a questionnaire asking respondents’ attitude towards the acts of violence committed by Front of Islamic Defence (FPI) as a radical Islamic movement. The data were analyzed by multiple regression and Structural Equation Modeling (SEM) using SPSS and M.Plus Program. This study concluded that strong identification as Muslims significantly influenced the supports to FPI acts through threat perception as a moderator variable. The study recommends for further investigation by employing qualitative approach to examine how independent variables influenced the supports for violence. KEY WORDS: Support, Violence, Identification